2021
DOI: 10.4103/ijabmr.ijabmr_609_20
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of trabeculectomy with collagen matrix implant versus mitomycin C in primary glaucoma: A comparative study

Abstract: Background: Glaucoma is a serious vision-threatening condition appropriately called as the silent killer of sight. The effect of postoperative fibrosis on success of filtration surgeries requires modulation of the wound healing process. Aim: The aim of the study was to compare trabeculectomy augmented with collagen matrix implant with mitomycin C in primary glaucoma. Materials and Methods: This prospective, longitudinal, hospital-based, analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…In the present study, the shallowing of AC and choroid ablation, the most prevalent complications in patients who underwent trabeculectomy, were reported in 17 (34 %) and 18 (36 %) patients, respectively. A similar prevalence of the shallowing of AC was reported in a recent study by Sharma et al (50), where the shallowing of AC was found in 39 % of patients who underwent trabeculectomy with MMC at a concentration of 0.4 mg/ml. On the contrary, other studies reported that fl at AC was present in less than 10 % of patients who had undergone trabeculectomy regardless of the form of MMC application (18,51).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, the shallowing of AC and choroid ablation, the most prevalent complications in patients who underwent trabeculectomy, were reported in 17 (34 %) and 18 (36 %) patients, respectively. A similar prevalence of the shallowing of AC was reported in a recent study by Sharma et al (50), where the shallowing of AC was found in 39 % of patients who underwent trabeculectomy with MMC at a concentration of 0.4 mg/ml. On the contrary, other studies reported that fl at AC was present in less than 10 % of patients who had undergone trabeculectomy regardless of the form of MMC application (18,51).…”
Section: Discussionsupporting
confidence: 87%